GAMELAN BALI DALAM KONSTELASI FILOSOFIS DAN ESTETIK - Sari, Anggy Paramitha (Sphatika: Jurnal Teologi, 2024)
Substantially, creativity cannot be separated from the elements of reason and the elements of human taste. Various arts and traditions that were born from human creativity eventually became the salience from each region of their maker. Gamelan is one of the many traditional Indonesian riches that was born from various considerations of thought, idea, notion, taste, and creativity of humans. Gamelan is a group of musical instruments with different beat patterns that are used in playing songs / ending. The emergence of the gamelan began when Hindu-Buddhist culture started to dominate the archipelago. There are several types of gamelan including Javanese gamelan, Sundanese gamelan, Banjar gamelan, Minang gamelan, and Balinese gamelan. All types of gamelan have their own uniqueness according to the area where it is developed. Gamelan is not only used as a musical accompaniment in traditional arts but is also used in various religious rituals. In Bali, almost all religious activities, especially in Hindu religious ceremonies, always use gamelan accompaniment. Balinese gamelan is one of the elements of the five voices (panca suara) that are always present in every yajna ceremony in Bali. These five voices cannot be separated from the Hindu aesthetic concept where each sound produced has a philosophical meaning. Balinese gamelan that is present in various Hindu rituals in Bali is not only for entertainment but also has a magical value that can vibrate the atmosphere. This article will discuss the philosophy of Balinese gamelan in aesthetic constellations.